Comparative morphology and physico-chemical properties of some forest and defrosted soils of Kerala - Sivadasan N (Department of Soil Science and Agricultural Chemistry, College of Agriculture, 1989)
In Kerala, continuous denudation of forests along the Western Ghats region has brought about hastening of the process of laterisation which becomes one of the major constraints to agricultural development. Deforestation of different types of forests such as deciduous, semi – evergreen, evergreen and shola may bring about laterisation to different extents. Deforestation and monoculture with different economically important species and plantation crops may delay or hasten the process of laterisation. The present study is, therefore an attempt to understand more about the effect of different monoculture vegetation such as cashew, eucalyptus, tea and acacia on soil properties in comparison with soils of adjoining virgin soils in deciduous, semi- evergreen, evergreen and shola forest ecosystems respectively. The present study reveals that deforestation has harmful effect on soil irrespective of the type of forest vegetation. It causes mechanical eluviation with higher migration of finer particles from surface downwards, increases bulk density of surface soil and lowers the aggregate stability of the soil. Organic carbon is found to be partly leached off and eroded off along with mineral soil. It is also burnt faster due to denudation. The contents of nitrogen and phosphorus increase while that of calcium and manganese decrease as a result of deforestation. Higher amounts of iron and aluminium are noticed in deforested soil than in virgin soils of the natural forests. The heavy mineral fraction constitutes from 2.5 to 27.6 per cent of the fine sand fraction. The dominant heavy minerals are the black opaques viz., ilmenite, red opaques such as hematite, limonite and goethite, sillimanite and zircon. The lighter fraction of the minerals is constituted mainly of quartz (22.6 to 97.5 per cent) with smaller amounts of feldspars and micas. The heavier fractionof the minerals are found to increase in soil due to deforestation brought about by residual accumulation. The influence of different monoculture / plantations on deforested soil varies with the type of vegetation. Increased root activity exhibited by tea and acacia at lower layers have strengthened the structural stability and improved the single value constants such as low bulk density, higher porosity and water holding capacity of the subsurface soil under these two plantations compared to soils under other plantations and virgin forests. The degree of weathering of soil varies with the type of vegetation. Based on the silt/clay ratio the soils studied can be arranged in the following order according to the observable factors on the degree of weathering : eucalyptus > tea > deciduous > semi – evergreen > cashew > shola > evergreen > acacia. Deforestation and monoculture with cashew, tea and acacia enhance the soil pH while monoculture with eucalyptus lowers the pH of the soil. Acacia is found to enrich the nitrogen status of the soil at a faster rate by its ability to fix atmospheric nitrogen. The study also reveals that ferrallitization advances in shola forest even if the level of organic matter in the surface soil is 5.19 per cent while no significant ferrallitization has been observed in acacia plantation having only 4.07 per cent organic matter in the surface soil though, both the soils fall under the same ecosystem. The critical role played by different type of vegetation in the manifestation of laterisation is yet to be studied. The micropedogenesis of kaoloinite from givvsite and silica in solution is clearly noticeable in laterised layers of the profile. Conversion of ferrouse to ferric iron the also observable in the thin section study of the soils. All soils are laterised with developing argillic horizonds and clay skins. The studies on soils of monoculture plantation crops such as cashew, eucalyptus, tea and acacia in comparison to virgin forest soils offers enough evidences from the present work to show that planted forests / plantation crops favour laterisation in general in comparison to virgin forests. Among the various types of monoculture, eucalyptus appears to enhance laterisation to the greatest extent while cashew and acacia favour laterisation to the least.